(untitled) - Klapita, Vladimir; Bukova, Bibiana; Sousek, Radovan (Doprava a spoje, 2005)
RFID chips technology is increasingly used in the praxis. This paper deals with the possibilities of RFID chips usage in rail freight transport, especially with monitoring of sending and movement of vehicles.